Gender Accessibility to Agricultural Production Resources and Extension Services amongst Rural Farmers in the North-East Nigeria (Global Journal of Science Frontier Research, 2023)
This paper reviewed gender issues on accessibility to agricultural production resources and extension services amongst rural farmers in the predominant crises regions of North-East Nigeria, The study applied qualitative analysis in reviewing related literatures, workshop proceedings, seminars, intervention projects, and situation reports on the crisis-torn regions of the Country to elicit cogent facts and figures, The findings revealed that there is a great deal of gender disparity in favor of the men folk as against women and youths in the accessibility to production resources and extension services in the affected regions of the study. This has not only affected their production output but also makes them vulnerable in crisis situations. The paper thus recommends strongly for gender mainstreaming policies towards ensuring equitable access to production resources and extension services in periods of emergencies in these regions.
Keywords: gender; accessibility; extension; production resources; rural farmers and crisis regions of north-east; nigeria